High-strength antibacterial plastic packaging bottle and preparation method thereof
By using polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide, high-strength antibacterial plastic packaging bottles, the plastic packaging bottles in the prior art are difficult to degrade and have low mechanical strength. The problem of short-term antibacterial effect has achieved green and environmentally friendly, high-strength and good antibacterial properties.
Patent Information
- Application Number
- CN202411575589.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing antibacterial plastic packaging bottles have problems such as difficulty in degradation, low mechanical strength, and short antibacterial effect.
High-strength antibacterial plastic packaging bottles are prepared by extrusion granulation, blow molding and coating protective coatings.
It has achieved green and environmentally friendly, high-strength and good antibacterial properties, and has a self-healing surface, which greatly extends the service life.
Smart Images

Figure BDA0005121712520000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, in particular to a high-strength antibacterial plastic packaging bottle and a preparation method thereof. Background Art
[0002] With the rapid development of society, people's attention to quality of life and food safety has gradually increased, thus forming requirements for green, healthy and safe. Antibacterial plastic packaging is a new type of packaging material that has gradually emerged in recent years. Its bactericidal and antibacterial properties can effectively improve the hygiene of the environment.
[0003] Existing common antibacterial plastic packaging is mostly made of polyethylene, polyvinyl chloride, and polypropylene as the base materials with antibacterial agents added. They are difficult to degrade and pollute the environment when discarded after large-scale use. At the same time, most plastic packaging bottles have problems such as short-lived antibacterial effects and low mechanical strength. Summary of the invention
[0004] The object of the present invention is to provide a high-strength antibacterial plastic packaging bottle and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a high-strength antibacterial plastic packaging bottle comprises the following steps:
[0007] S1: polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide are mixed, extruded into granules, and blow-molded to obtain a base member;
[0008] S2: Preparation of protective coatings using composite zinc oxide and soybean oil-based self-healing waterborne polyurethane;
[0009] S3: coating the protective coating on the surface of the base member and curing the coating to obtain a high-strength antibacterial plastic packaging bottle.
[0010] Furthermore, the curing working conditions are: keeping warm at 90-110°C for 1-2 hours.
[0011] Furthermore, the mass ratio of polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide is 79:10:4:7.
[0012] Furthermore, the mass ratio of the composite zinc oxide to the soybean oil-based self-healing waterborne polyurethane in the protective coating is 9-14%.
[0013] Further, the preparation of composite zinc oxide comprises the following steps:
[0014] (1) Mix zinc nitrate hexahydrate, carbamide, and deionized water, add polyoxyethylene polyoxypropylene ether block copolymer and sucrose, adjust the pH of the solution to 4-5, stir for 1-2 hours, transfer to a reaction kettle, heat to 88-92° C. and keep warm for 22-24 hours, cool, centrifuge, wash, dry, use a Soxhlet extractor, use anhydrous ethanol as an extractant to extract for 12 hours, dry, and keep warm at 270° C. for 1.5 hours to obtain mesoporous nano zinc oxide;
[0015] (2) Mix tea polyphenols and deionized water, add a mixture of mesoporous nano zinc oxide and deionized water, ultrasonically stir for 1-3 minutes, vacuum stir for 20-30 minutes, add a mixture of carboxymethyl chitosan and deionized water, ultrasonically disperse for 10-15 minutes, add a mixture of liquid paraffin and Span-80, stir for 20-30 minutes, add glutaraldehyde solution, heat to 40-50° C. and keep warm for 1-2 hours, adjust the pH value of the solution to 9-10, heat to 68-72° C. and keep warm for 2-3 hours, wash with acetone, petroleum ether, and anhydrous ethanol in turn, and dry to obtain zinc oxide composite microspheres;
[0016] (3) Mixing the epoxy compound containing Si-O segments, zinc oxide composite microspheres and ethanol, heating to 88-92° C., adding zinc acetate, stirring for 1-2 hours, cooling, washing and drying to obtain composite zinc oxide.
[0017] Furthermore, the preparation of soybean oil-based self-healing waterborne polyurethane comprises the following steps:
[0018] 1) Mix polyethylene glycol monomethyl ether and tetrafluoroboric acid, raise the temperature to 60-65°C and keep warm for 30-40 minutes, add epoxidized soybean oil, continue to keep warm for 110-120 minutes, add to ethyl acetate, add saturated brine to extract, dry with anhydrous magnesium sulfate, filter, and rotary evaporate to obtain soybean oil-based polyol;
[0019] 2) Under a nitrogen atmosphere, soybean oil-based polyol, polytetramethylene glycol and isophorone diisocyanate are mixed, the temperature is raised to 75-80°C and kept warm for 8-12 minutes, 2,2-bis(hydroxymethyl)propionic acid, dibutyltin dilaurate and N,N-dimethylformamide are added, and the temperature is kept warm for 1-2 hours, a mixed solution of Si-O segment epoxy compound and N,N-dimethylformamide is added, and the temperature is kept warm for 1-2 hours, the temperature is lowered to 55-57°C, 1,4-butanediol, dithiodiethanol and butanone are added, and the temperature is kept warm for 1-2 hours, the temperature is lowered to 33-38°C, triethylamine is added and kept warm for 10-20 minutes, a mixed solution of ethylenediamine, tetraethylenepentamine and deionized water is poured in, and the mixture is emulsified in an ice water bath for 10-15 minutes, and rotary evaporated to obtain a soybean oil-based self-healing waterborne polyurethane.
[0020] Furthermore, the mass ratio of the Si-O segment-containing epoxy compound to the zinc oxide composite microspheres is 1:1.5.
[0021] Furthermore, the mass ratio of soybean oil-based polyol, polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, epoxy compound containing Si-O chain segment, and dithiodiethanol is 8:3:10.2:1:2:1.8.
[0022] Further, the preparation of the epoxy compound containing Si-O chain segments comprises the following steps:
[0023] Under a nitrogen atmosphere, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ethanol are mixed, epichlorohydrin is added, the temperature is raised to 53-57°C and kept warm for 4-5 hours, cooled to 28-32°C, sodium hydroxide solution is added, and the temperature is kept warm for 2 hours. The mixture is filtered, rotary evaporated, washed, and dried to obtain an epoxy compound containing Si-O segments.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention provides a high-strength antibacterial plastic packaging bottle and a preparation method thereof. Through component and process design, a green and environmentally friendly plastic packaging bottle with high strength, good antibacterial property and a self-repairing surface is prepared.
[0026] The invention is based on the concept of green environmental protection, selects degradable polylactic acid as the base material of the plastic packaging bottle, and in order to solve the brittleness problem of polylactic acid, polybutylene succinate with high tension, strong toughness and excellent biocompatibility is blended as a toughening agent, and in order to improve the compatibility of polylactic acid and polybutylene succinate, epoxy soybean oil is selected as a compatibilizer, and in order to improve the antibacterial property of the plastic packaging bottle, zinc oxide and tea polyphenols are selected as antibacterial agents to achieve a broad-spectrum antibacterial effect, and in order to improve the uniformity and thermal stability of the dispersion of zinc oxide and tea polyphenols in the plastic packaging bottle to achieve a lasting antibacterial effect, the invention firstly uses a polyoxyethylene polyoxypropylene ether block copolymer and sucrose The mesoporous nano zinc oxide was prepared by a hydrothermal method with ZnO as a template, and the natural antibacterial agent tea polyphenols was carried on the mesoporous nano zinc oxide as a carrier. Then, under the action of the cross-linking agent glutaraldehyde, the biocompatible and easily degradable carboxymethyl chitosan was used to coat the microspheres to obtain zinc oxide composite microspheres, thereby overcoming the problem of uncontrolled release of tea polyphenols. Then, under the catalysis of zinc acetate, epoxy compounds containing Si-O segments were grafted to obtain composite zinc oxide with dynamic ester bonds and epoxy groups. The epoxy groups were used to react with the terminal hydroxyl / carboxyl groups of polylactic acid and polybutylene succinate during the melt blending process to enhance the bonding strength between the microspheres and the base material, thereby achieving a lasting antibacterial effect.
[0027] The epoxy compound containing Si-O segments is prepared from 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and epichlorohydrin. Introducing the epoxy compound containing Si-O segments into the composite zinc oxide helps to improve the toughness of the plastic bottle.
[0028] In order to give the surface of plastic bottles excellent resistance to mechanical damage and improve the sealing and antibacterial durability of plastic bottles, a protective coating was prepared using composite zinc oxide and soybean oil-based self-healing water-based polyurethane and coated on the surface of the substrate to construct a green, antibacterial, antifouling and self-healing surface.
[0029] By hydroxyl ring-opening epoxidation of soybean oil, polyethylene glycol antifouling groups are coupled on the side chains to obtain soybean oil-based polyols, which are then used as raw materials with polytetramethylene ether glycol and isophorone diisocyanate to prepare polyurethane prepolymers. Under the action of a catalyst, 2,2-bis(hydroxymethyl)propionic acid is used as a hydrophilic chain extender, epoxy compounds containing Si-O segments are used as modifiers, 1,4-butanediol and dithiodiethanol are used as end-capping agents, triethylamine is used as a neutralizer, and ethylenediamine and tetraethylenepentamine are used as amine cross-linking agents to prepare soybean oil-based self-healing waterborne polyurethanes. Composite zinc oxide is then used as a filler to give the base component a green, antibacterial, antifouling and self-healing surface, greatly extending the service life of plastic bottles. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0033] Embodiment 1: A method for preparing a high-strength antibacterial plastic packaging bottle, comprising the following steps:
[0034] S1: polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide are mixed, extruded into granules, and blow-molded to obtain a base member;
[0035] The mass ratio of polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide is 79:10:4:7;
[0036] The preparation of the composite zinc oxide comprises the following steps:
[0037] (1) 2.2 g of zinc nitrate hexahydrate, 12 g of carbamide, and 200 mL of deionized water were mixed, 0.72 g of polyoxyethylene polyoxypropylene ether block copolymer and 0.72 g of sucrose were added, the pH of the solution was adjusted to 4, stirred for 1 hour, transferred to a reaction kettle, heated to 88° C. and kept warm for 24 hours, cooled, centrifuged, washed, dried, and extracted with anhydrous ethanol using a Soxhlet extractor for 12 hours, dried, and kept warm at 270° C. for 1.5 hours to obtain mesoporous nano zinc oxide;
[0038] (2) 6 g of tea polyphenols and 60 mL of deionized water were mixed, and a mixture of 1 g of mesoporous nano zinc oxide and 40 mL of deionized water was added, and ultrasonic stirring was performed for 1 min, and vacuum stirring was performed for 20 min, and a mixture of 2 g of carboxymethyl chitosan and 80 mL of deionized water was added, and ultrasonic dispersion was performed for 10 min, and a mixture of 300 mL of liquid paraffin and 100 mL of Span-80 was added, and stirring was performed for 20 min, and 4 mL of 7% glutaraldehyde solution was added, and the temperature was raised to 40° C. and kept warm for 2 h, and the pH value of the solution was adjusted to 9, and the temperature was raised to 68° C. and kept warm for 3 h, and the zinc oxide composite microspheres were washed and dried with acetone, petroleum ether, and anhydrous ethanol in turn, to obtain zinc oxide composite microspheres;
[0039] (3) 2 g of Si-O segment-containing epoxy compound, 3 g of zinc oxide composite microspheres, and 30 mL of ethanol were mixed, heated to 88° C., 0.13 g of zinc acetate was added, stirred for 1 h, cooled, washed, and dried to obtain composite zinc oxide;
[0040] The preparation of the Si-O segment-containing epoxy compound comprises the following steps:
[0041] Under a nitrogen atmosphere, 1.4 mL of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 50 mL of ethanol were mixed, 15.6 mL of epichlorohydrin was added, the temperature was raised to 53°C and kept warm for 5 h, cooled to 28°C, 2 g of a 50% sodium hydroxide solution was added, the temperature was kept warm for 2 h, filtered, rotary evaporated, washed, and dried to obtain an epoxy compound containing a Si-O segment;
[0042] S2: Preparation of protective coatings using composite zinc oxide and soybean oil-based self-healing waterborne polyurethane;
[0043] The mass ratio of composite zinc oxide and soybean oil-based self-healing waterborne polyurethane in the protective coating is 9%;
[0044] The preparation of soybean oil-based self-healing waterborne polyurethane includes the following steps:
[0045] 1) Mix 5 g of polyethylene glycol monomethyl ether and 0.01 g of tetrafluoroboric acid, heat to 60° C. and keep warm for 40 min, add 6.5 g of epoxidized soybean oil, continue to keep warm for 110 min, add to 5 mL of ethyl acetate, add 50 mL of saturated brine to extract, dry with anhydrous magnesium sulfate, filter, and rotary evaporate to obtain soybean oil-based polyol;
[0046] 2) Under nitrogen atmosphere, 8 g soybean oil-based polyol, 3 g polytetramethylene glycol, and 10.2 g isophorone diisocyanate were mixed, heated to 75 °C for 12 min, 1 g 2,2-bis(hydroxymethyl)propionic acid, 3 drops of dibutyltin dilaurate, and 5 mL N,N-dimethylformamide were added, and the mixture was kept warm for 1 h. 2 g of a Si-O segment epoxy compound and 5 mL N,N-dimethylformamide were added, and the mixture was kept warm for 1 h. h, cool to 55°C, add 0.6g 1,4-butanediol, 1.8g dithiodiethanol, and 6mL butanone, continue to keep warm for 1h, cool to 33°C, add 0.1g triethylamine and keep warm for 10min, pour in a mixture of 0.2g ethylenediamine, 0.2g tetraethylenepentamine, and deionized water, emulsify at 3000r / min for 10min in an ice water bath, and rotary evaporate to obtain a soybean oil-based self-healing waterborne polyurethane with a solid content of 18%;
[0047] S3: coating the protective coating on the surface of the base member and curing the coating to obtain a high-strength antibacterial plastic packaging bottle; the curing working conditions are: keeping the temperature at 90° C. for 2 hours.
[0048] Embodiment 2: A method for preparing a high-strength antibacterial plastic packaging bottle, comprising the following steps:
[0049] S1: polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide are mixed, extruded into granules, and blow-molded to obtain a base member;
[0050] The mass ratio of polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide is 79:10:4:7;
[0051] The preparation of the composite zinc oxide comprises the following steps:
[0052] (1) 2.2 g of zinc nitrate hexahydrate, 12 g of carbamide, and 200 mL of deionized water were mixed, 0.72 g of polyoxyethylene polyoxypropylene ether block copolymer and 0.72 g of sucrose were added, the pH of the solution was adjusted to 4.5, stirred for 1.5 h, transferred to a reactor, heated to 90 ° C and kept warm for 23 h, cooled, centrifuged, washed, dried, and extracted with anhydrous ethanol using a Soxhlet extractor for 12 h, dried, and kept warm at 270 ° C for 1.5 h to obtain mesoporous nano zinc oxide;
[0053] (2) 6 g of tea polyphenols and 60 mL of deionized water were mixed, and a mixture of 1 g of mesoporous nano zinc oxide and 40 mL of deionized water was added, and ultrasonic stirring was performed for 2 min, and vacuum stirring was performed for 25 min, and a mixture of 2 g of carboxymethyl chitosan and 80 mL of deionized water was added, and ultrasonic dispersion was performed for 13 min, and a mixture of 300 mL of liquid paraffin and 100 mL of Span-80 was added, and stirring was performed for 25 min, and 4 mL of 7% glutaraldehyde solution was added, and the temperature was raised to 45° C. and kept warm for 1.5 h, and the pH value of the solution was adjusted to 9.5, and the temperature was raised to 70° C. and kept warm for 2.5 h, and washed and dried with acetone, petroleum ether, and anhydrous ethanol in turn to obtain zinc oxide composite microspheres;
[0054] (3) 2 g of Si-O segment-containing epoxy compound, 3 g of zinc oxide composite microspheres, and 30 mL of ethanol were mixed, heated to 90° C., 0.13 g of zinc acetate was added, stirred for 1.5 h, cooled, washed, and dried to obtain composite zinc oxide;
[0055] The preparation of the Si-O segment-containing epoxy compound comprises the following steps:
[0056] Under a nitrogen atmosphere, 1.4 mL of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 50 mL of ethanol were mixed, 15.6 mL of epichlorohydrin was added, the temperature was raised to 55°C and kept warm for 4.5 h, cooled to 30°C, 2 g of a 50% sodium hydroxide solution was added, the temperature was kept warm for 2 h, filtered, rotary evaporated, washed, and dried to obtain an epoxy compound containing a Si-O segment;
[0057] S2: Preparation of protective coatings using composite zinc oxide and soybean oil-based self-healing waterborne polyurethane;
[0058] The mass ratio of composite zinc oxide and soybean oil-based self-healing waterborne polyurethane in the protective coating is 12%;
[0059] The preparation of soybean oil-based self-healing waterborne polyurethane includes the following steps:
[0060] 1) Mix 5 g of polyethylene glycol monomethyl ether and 0.01 g of tetrafluoroboric acid, heat to 60-65° C. and keep warm for 30-40 min, add 6.5 g of epoxidized soybean oil, continue to keep warm for 110-120 min, add to 5 mL of ethyl acetate, add 50 mL of saturated brine to extract, dry with anhydrous magnesium sulfate, filter, and rotary evaporate to obtain soybean oil-based polyol;
[0061] 2) Under nitrogen atmosphere, 8g soybean oil-based polyol, 3g polytetramethylene glycol, and 10.2g isophorone diisocyanate were mixed, heated to 78°C and kept warm for 10min, 1g 2,2-bis(hydroxymethyl)propionic acid, 3 drops of dibutyltin dilaurate, and 5mL N,N-dimethylformamide were added, and the mixture was kept warm for 1.5h. A mixture of 2g Si-O segment epoxy compound and 5mL N,N-dimethylformamide was added, and the mixture was kept warm for 1. 5h, cool to 56°C, add 0.6g 1,4-butanediol, 1.8g dithiodiethanol, and 6mL butanone, continue to keep warm for 1.5h, cool to 35°C, add 0.1g triethylamine and keep warm for 15min, pour in a mixture of 0.2g ethylenediamine, 0.2g tetraethylenepentamine, and deionized water, emulsify at 3000r / min for 13min in an ice water bath, and rotary evaporate to obtain a soybean oil-based self-healing waterborne polyurethane with a solid content of 18%;
[0062] S3: coating the protective coating on the surface of the base member and curing the coating to obtain a high-strength antibacterial plastic packaging bottle; the curing working conditions are: keeping the temperature at 100° C. for 1.5 hours.
[0063] Embodiment 3: A method for preparing a high-strength antibacterial plastic packaging bottle, comprising the following steps:
[0064] S1: polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide are mixed, extruded into granules, and blow-molded to obtain a base member;
[0065] The mass ratio of polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide is 79:10:4:7;
[0066] The preparation of the composite zinc oxide comprises the following steps:
[0067] (1) 2.2 g of zinc nitrate hexahydrate, 12 g of carbamide, and 200 mL of deionized water were mixed, 0.72 g of polyoxyethylene polyoxypropylene ether block copolymer and 0.72 g of sucrose were added, the pH of the solution was adjusted to 5, stirred for 2 h, transferred to a reaction kettle, heated to 92 ° C and kept warm for 22 h, cooled, centrifuged, washed, dried, and extracted with anhydrous ethanol using a Soxhlet extractor for 12 h, dried, and kept warm at 270 ° C for 1.5 h to obtain mesoporous nano zinc oxide;
[0068] (2) 6 g of tea polyphenols and 60 mL of deionized water were mixed, and a mixture of 1 g of mesoporous nano zinc oxide and 40 mL of deionized water was added, and ultrasonic stirring was performed for 3 min, and vacuum stirring was performed for 30 min, and a mixture of 2 g of carboxymethyl chitosan and 80 mL of deionized water was added, and ultrasonic dispersion was performed for 15 min, and a mixture of 300 mL of liquid paraffin and 100 mL of Span-80 was added, and stirring was performed for 30 min, and 4 mL of 7% glutaraldehyde solution was added, and the temperature was raised to 50° C. and kept warm for 1 h, and the pH value of the solution was adjusted to 10, and the temperature was raised to 72° C. and kept warm for 2 h, and washed and dried with acetone, petroleum ether, and anhydrous ethanol in turn to obtain zinc oxide composite microspheres;
[0069] (3) 2 g of Si-O segment-containing epoxy compound, 3 g of zinc oxide composite microspheres, and 30 mL of ethanol were mixed, heated to 92° C., 0.13 g of zinc acetate was added, stirred for 2 h, cooled, washed, and dried to obtain composite zinc oxide;
[0070] The preparation of the Si-O segment-containing epoxy compound comprises the following steps:
[0071] Under a nitrogen atmosphere, 1.4 mL of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 50 mL of ethanol were mixed, 15.6 mL of epichlorohydrin was added, the temperature was raised to 57°C and kept warm for 4 h, cooled to 32°C, 2 g of a 50% sodium hydroxide solution was added, the temperature was kept warm for 2 h, filtered, rotary evaporated, washed, and dried to obtain an epoxy compound containing a Si-O segment;
[0072] S2: Preparation of protective coatings using composite zinc oxide and soybean oil-based self-healing waterborne polyurethane;
[0073] The mass ratio of composite zinc oxide and soybean oil-based self-healing waterborne polyurethane in the protective coating is 9-14%;
[0074] The preparation of soybean oil-based self-healing waterborne polyurethane includes the following steps:
[0075] 1) Mix 5 g of polyethylene glycol monomethyl ether and 0.01 g of tetrafluoroboric acid, heat to 65° C. and keep warm for 40 min, add 6.5 g of epoxidized soybean oil, continue to keep warm for 120 min, add to 5 mL of ethyl acetate, add 50 mL of saturated brine to extract, dry with anhydrous magnesium sulfate, filter, and rotary evaporate to obtain soybean oil-based polyol;
[0076] 2) Under nitrogen atmosphere, 8g soybean oil-based polyol, 3g polytetramethylene glycol, and 10.2g isophorone diisocyanate were mixed, heated to 80°C for 8min, 1g 2,2-bis(hydroxymethyl)propionic acid, 3 drops of dibutyltin dilaurate, and 5mL N,N-dimethylformamide were added, and the mixture was kept warm for 2h. A mixture of 2g Si-O segment epoxy compound and 5mL N,N-dimethylformamide was added, and the mixture was kept warm for 2h. , cool to 57°C, add 0.6g 1,4-butanediol, 1.8g dithiodiethanol, and 6mL butanone, continue to keep warm for 2h, cool to 38°C, add 0.1g triethylamine and keep warm for 20min, pour in a mixture of 0.2g ethylenediamine, 0.2g tetraethylenepentamine, and deionized water, emulsify at 3000r / min for 15min in an ice water bath, and rotary evaporate to obtain a soybean oil-based self-healing waterborne polyurethane with a solid content of 18%;
[0077] S3: coating the protective coating on the surface of the base member and curing the coating to obtain a high-strength antibacterial plastic packaging bottle; the curing working conditions are: keeping warm at 110° C. for 1 hour.
[0078] Comparative Example 1: Taking Example 3 as the control group, mesoporous nano zinc oxide was used to replace the composite zinc oxide, and other processes were normal.
[0079] Comparative Example 2: Example 3 was used as a control group, soybean oil-based polyol was not prepared, and other processes were normal.
[0080] Comparative Example 3: Example 3 was used as a control group, in which no Si-O segment-containing epoxy compound was prepared, and other processes were normal.
[0081] In the embodiments and comparative examples, the thickness of the base member is 0.8 mm, and the thickness of the protective coating after being coated on the surface of the base member and cured is 0.2 mm.
[0082] Sources of raw materials used (for demonstration purposes only):
[0083] Polylactic acid JS2894: Hubei Jusheng Technology Co., Ltd.; polybutylene succinate 05131: Dongguan Shenghao Plastic Raw Materials Co., Ltd.; Epoxidized soybean oil 197: Zibo Lishuo Chemical Trading Co., Ltd.; polyoxyethylene polyoxypropylene ether block copolymer 2023: Shanxi Jinyang Pharmaceutical Excipients Co., Ltd.; 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane XK2342: Hubei Xinkang Pharmaceutical Chemical Co., Ltd.; tetrafluoroboric acid 16872-11-0: Hubei Chengfeng Chemical Co., Ltd.; zinc nitrate hexahydrate Z111703, carbodiimide U111897, sucrose S112228, tea polyphenols T418534, carboxymethyl chitosan C304738, liquid paraffin P304684, S pan-80S110840, glutaraldehyde G105905, epichlorohydrin E108182, polyethylene glycol monomethyl ether M109717, polytetramethylene ether glycol P117874, isophorone diisocyanate I109582, dibutyltin dilaurate D100274, N,N-dimethylformamide D111999, 2,2-bis(hydroxymethyl)propionic acid B104539, 1,4-butanediol B110391, triethylamine T103285, ethylenediamine E112132, dithiodiethanol B152479, tetraethylenepentamine T103795: Aladdin reagent; ethanol, acetone, petroleum ether, zinc acetate, sodium hydroxide, ethyl acetate, saline, magnesium sulfate, butanone, analytical grade: Sinopharm reagent.
[0084] Performance test: The plastic packaging bottles prepared in the embodiments and comparative examples were tested:
[0085] Tensile strength test: electronic universal testing machine was used for testing, the sample was 80mm long and 40mm wide, the test temperature was 25℃, and the tensile rate was 5mm / min; Self-repair rate: a scratch of 1mm long, 2μm wide and 0.2mm deep was made on the surface of the sample, kept at 50℃ for 12h, and the scratch length was observed with an electron microscope. The self-repair rate = (L 划痕初始长度 -L 保温后划痕长度 ) / L 划痕初始长度 ×100%; Antibacterial persistence: ATCC 6538 Staphylococcus aureus was used as the test strain, and the test was carried out with reference to ISO22196:2007, using the plate counting method, and the test was carried out after 20 standard water washes; the results are shown in Table 1;
[0086] Table 1
[0087]
[0088] The present invention provides a high-strength antibacterial plastic packaging bottle and a preparation method thereof. Through component and process design, a green, environmentally friendly, high-strength, good antibacterial plastic packaging bottle with a self-repairing surface is prepared. In Table 1, / indicates that the item has not been tested.
[0089] By comparing Example 3 with Comparative Examples 1 and 3, it can be seen that zinc oxide and tea polyphenols are selected as antibacterial agents to achieve a broad-spectrum antibacterial effect. In order to improve the uniformity and thermal stability of the dispersion of zinc oxide and tea polyphenols in plastic packaging bottles and achieve a lasting antibacterial effect, the present invention first uses polyoxyethylene polyoxypropylene ether block copolymers and sucrose as templates, adopts a hydrothermal method to prepare mesoporous nano zinc oxide, uses mesoporous nano zinc oxide as a carrier to carry the natural antibacterial agent tea polyphenols, and then, under the action of a cross-linking agent glutaraldehyde, uses biocompatible and easily degradable carboxymethyl chitosan for coating to obtain zinc oxide composite microspheres, thereby overcoming the problem of uncontrolled release of tea polyphenols; and then, under the catalytic action of zinc acetate, grafts Si-O segment-containing epoxy compounds to obtain composite zinc oxide having dynamic ester bonds and epoxy groups, and utilizes its epoxy groups to react with the terminal hydroxyl / carboxyl groups of polylactic acid and polybutylene succinate during melt blending to enhance its bonding strength with the base material, thereby achieving a lasting antibacterial effect.
[0090] The epoxy compound containing Si-O segments is prepared from 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and epichlorohydrin. Introducing the epoxy compound containing Si-O segments into the composite zinc oxide helps to improve the toughness of the plastic bottle.
[0091] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that soybean oil-based polyol is obtained by coupling polyethylene glycol antifouling groups on the side chains through hydroxyl ring-opening epoxidation of soybean oil, and the soybean oil-based polyol is used as raw materials with polytetramethylene ether glycol and isophorone diisocyanate to prepare polyurethane prepolymers. Under the action of a catalyst, 2,2-bis(hydroxymethyl)propionic acid is used as a hydrophilic chain extender, an epoxy compound containing Si-O segments is used as a modifier, 1,4-butanediol and dithiodiethanol are used as end-capping agents, triethylamine is used as a neutralizing agent, and ethylenediamine and tetraethylenepentamine are used as amine cross-linking agents to prepare soybean oil-based self-healing waterborne polyurethane. Then, composite zinc oxide is used as a filler to give the base component a green, environmentally friendly, antibacterial, antifouling and self-healing surface, thereby greatly extending the service life of the plastic bottle.
[0092] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-strength antibacterial plastic packaging bottle, characterized in that: The following steps are involved: S1: polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide are mixed, extruded into granules, and blow-molded to obtain a base member; S2: Preparation of protective coatings using composite zinc oxide and soybean oil-based self-healing waterborne polyurethane; S3: coating the protective coating on the surface of the base member and curing the coating to obtain a high-strength antibacterial plastic packaging bottle.
2. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 1, characterized in that: The working conditions for curing are: keeping warm at 90-110℃ for 1-2h.
3. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 1, characterized in that: The mass ratio of polylactic acid, polybutylene succinate, epoxy soybean oil and composite zinc oxide is 79:10:4:
7.
4. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 1, characterized in that: The mass ratio of composite zinc oxide and soybean oil-based self-repairing waterborne polyurethane in the protective coating is 9-14%.
5. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 1, characterized in that: The preparation of the composite zinc oxide comprises the following steps: (1) Mix zinc nitrate hexahydrate, carbamide, and deionized water, add polyoxyethylene polyoxypropylene ether block copolymer and sucrose, adjust the pH of the solution to 4-5, stir for 1-2 hours, transfer to a reaction kettle, heat to 88-92° C. and keep warm for 22-24 hours, cool, centrifuge, wash, dry, use a Soxhlet extractor, use anhydrous ethanol as an extractant to extract for 12 hours, dry, and keep warm at 270° C. for 1.5 hours to obtain mesoporous nano zinc oxide; (2) Mix tea polyphenols and deionized water, add a mixture of mesoporous nano zinc oxide and deionized water, ultrasonically stir for 1-3 minutes, vacuum stir for 20-30 minutes, add a mixture of carboxymethyl chitosan and deionized water, ultrasonically disperse for 10-15 minutes, add a mixture of liquid paraffin and Span-80, stir for 20-30 minutes, add glutaraldehyde solution, heat to 40-50° C. and keep warm for 1-2 hours, adjust the pH value of the solution to 9-10, heat to 68-72° C. and keep warm for 2-3 hours, wash with acetone, petroleum ether, and anhydrous ethanol in turn, and dry to obtain zinc oxide composite microspheres; (3) Mixing the Si-O segment-containing epoxy compound, zinc oxide composite microspheres, and ethanol, heating to 88-92° C., adding zinc acetate, stirring for 1-2 hours, cooling, washing, and drying to obtain composite zinc oxide.
6. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 1, characterized in that: The preparation of the soybean oil-based self-repairing waterborne polyurethane comprises the following steps: 1) Mix polyethylene glycol monomethyl ether and tetrafluoroboric acid, raise the temperature to 60-65°C and keep warm for 30-40 minutes, add epoxidized soybean oil, continue to keep warm for 110-120 minutes, add to ethyl acetate, add saturated brine to extract, dry with anhydrous magnesium sulfate, filter, and rotary evaporate to obtain soybean oil-based polyol; 2) Under a nitrogen atmosphere, soybean oil-based polyol, polytetramethylene glycol and isophorone diisocyanate are mixed, the temperature is raised to 75-80°C and kept warm for 8-12 minutes, 2,2-bis(hydroxymethyl)propionic acid, dibutyltin dilaurate and N,N-dimethylformamide are added, and the temperature is kept warm for 1-2 hours, a mixed solution of Si-O segment epoxy compound and N,N-dimethylformamide is added, and the temperature is kept warm for 1-2 hours, the temperature is lowered to 55-57°C, 1,4-butanediol, dithiodiethanol and butanone are added, and the temperature is kept warm for 1-2 hours, the temperature is lowered to 33-38°C, triethylamine is added and kept warm for 10-20 minutes, a mixed solution of ethylenediamine, tetraethylenepentamine and deionized water is poured in, and the mixture is emulsified in an ice water bath for 10-15 minutes, and rotary evaporated to obtain a soybean oil-based self-healing waterborne polyurethane.
7. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 5, characterized in that: The mass ratio of the Si-O segment epoxy compound to the zinc oxide composite microspheres is 1:1.
5.
8. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 6, characterized in that: The mass ratio of soybean oil-based polyol, polytetramethylene glycol, isophorone diisocyanate, 2,2-bis(hydroxymethyl)propionic acid, epoxy compound containing Si-O chain segment, and dithiodiethanol is 8:3:10.2:1:2:1.
8.
9. The method for preparing a high-strength antibacterial plastic packaging bottle according to claim 5 or 6, characterized in that: The preparation of the Si-O segment-containing epoxy compound comprises the following steps: Under a nitrogen atmosphere, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ethanol are mixed, epichlorohydrin is added, the temperature is raised to 53-57°C and kept warm for 4-5 hours, cooled to 28-32°C, sodium hydroxide solution is added, and the temperature is kept warm for 2 hours. The mixture is filtered, rotary evaporated, washed, and dried to obtain an epoxy compound containing Si-O segments.
10. A high-strength antibacterial plastic packaging bottle, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
PH responsive intelligent controlled-release antibacterial degradable packaging film and preparation method and application thereof
CN113601933A
Bio-based waterborne polyurethane material with self-repairing performance and preparation method thereof
CN115197394A
Transparent plastic bottle suitable for returnable use
JP2023157233A
Cited By
High-precision wear-resistant filtering material coated with nano coating and preparation method of high-precision wear-resistant filtering material
CN120037719A
A high-precision wear-resistant filter material coated with a nano coating and a preparation method thereof
CN120037719B